Enhanced Continental Weathering Triggered the Anoxia of Seawater and Mass Extinctions During the Late Ordovician - Pan Tang; Xiangrong Yang; Detian Yan (Journal of Marine Science and Engineering)
During the Late Ordovician period, changes in climate and mass extinctions were observed; however, the factors influencing these phenomena have not been fully understood. In order to understand the relationships among redox water conditions, climates, and mass extinctions in the Late Ordovician, this study analyzes the chemical index of alteration (CIA) in shales and 87Sr/86Sr in carbonate leachates as proxies of changes in chemical weathering intensity and chemical weathering rate in the Late Ordovician (mainly from Katian to Hirnantian). The results show that an enhanced chemical weathering rate (increased 87Sr/86Sr ratios) and decreased chemical weathering intensity (decreased CIA values) characterized the late Katian, which might be attributed to the global orogenesis and enhanced precipitation/runoff under the warming climate (late-Boda warming). This enhanced chemical weathering rate contributed to the CO2 drawdown in the P. pacificus biozone, corresponding to the initiation of cooling and further glaciation. Meanwhile, the enhanced weathering-induced high primary productivity could have contributed to the expansion of anoxic seawater in the Katian, which further caused the Katian extinction. The Hirnantian Glaciation was characterized by high 87Sr/86Sr ratios in carbonates and extremely low CIA values in shales, which were likely related to the exposure of continents during low sea level and the glacial grinding of unweathered rocks. This study shows that the highest denudation rate and lowest chemical weathering intensity in the Hirnantian stage might have resulted in enhanced CO2 release and contributed to the end of glaciation.